2020
DOI: 10.1016/j.cegh.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Quality of services provided by public funded ambulance program: Experience from a northern state in India

Abstract: Background: Ambulance Services are vital in providing pre-hospital treatment and care to help regain life. Timely and safe transport of patients from the emergency scene to the appropriate healthcare facility for further care is a complex process. Administering emergency services in minimal time is a challenge in a country with basic lacunae in infrastructure", making the role of EMTs (emergency medical technicians) and ambulance quality vital in saving lives. Methods: A descriptive cross-sectional study using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…During last year, the Ministry of Poverty Alleviation and Social Protection planned the initiatives, including SNF implementation, to improve the nutritional status of children under two years and pregnant women [ 35 ]. Public emergency services such as ambulances would help mitigate services to prone areas, which may help reduce the disease burden [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…During last year, the Ministry of Poverty Alleviation and Social Protection planned the initiatives, including SNF implementation, to improve the nutritional status of children under two years and pregnant women [ 35 ]. Public emergency services such as ambulances would help mitigate services to prone areas, which may help reduce the disease burden [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A spatial analysis (35) from India revealed that literacy plays a significant role in ANC visits while illiteracy and poverty are important risk factors for having less or no prenatal care (36). Emergency transport services also play a vital role in ANC (37,38), such as a dedicated Janani express (free transportation under Janani Sishu Suraksha 192 Karyakaram). Findings from the path also revealed that diarrhea and exclusive breastfeeding had a significant positive effect on wasting among children.…”
Section: Discussionmentioning
confidence: 99%
“…Layanan Ambulans sangat penting dalam menyediakan perawatan dan perawatan pra-rumah sakit untuk membantu mendapatkan kembali kehidupan. Pengangkutan pasien yang tepat waktu dan aman dari tempat gawat darurat ke fasilitas perawatan kesehatan yang sesuai untuk perawatan lebih lanjut adalah proses yang kompleks (Tiwary, Nilima, Majumdar, Singh, & Khan, 2020 Berdasarkan tabel 5 menunjukkan waktu tempuh antara lokasi berangkat dengan instalasi gawat darurat RSUD Ratu Zaleha didapatkan hasil 17 informan (56,57%) ≥165 menit. Waktu emas (golden window) dalam penanganan stroke adalah ± 3 jam, artinya dalam 3 jam awal setelah mendapatkan serangan stroke, pasien harus segera mendapatkan terapi secara komprehensif dan optimal dari tim gawat darurat rumah sakit untuk mendapatkan hasil pengobatan yang optimal (Bahnasy et al, 2019).…”
Section: Alasan Penggunaan Transportasiunclassified